The Effect Of Egg White On Perineum Wound Healing in Pospartum Mothers at the Pratama Nining Pelawati Clinic - Meria Turnip; Irma Nurianti; Reni Aprinawaty Sirait (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Perineal laceration is trauma to the perineum due to tearing of the birth canal or due to an episiotomy at the time of expulsion of the fetus from the uterus. One of the causes of infection and bleeding is perineal laceration. Old perineal laceration wound healing can increase the risk of infection so it is necessary to fulfill nutritional intake, especially protein which will help the growth of new cells in the perineal laceration wound so that the perineal laceration healing process can be accelerated. This study aims to determine whether the administration of boiled egg white has an effect on the healing of perineal lacerations in postpartum mothers at the Pratama Nining Pelawati Clinic. This type of research uses a quasi-experimental design with One Group Pretest and Posttest design. The population and sample in this study were all postpartum mothers on the first day at the Pratama Nining Pelawati Clinic, totaling 20 people with a total sampling technique. Data were collected using a check list sheet. The results showed that the majority of respondents who consumed boiled egg whites had fast perineal lacerations healing as many as 17 people (85%). Based on the results of data analysis with the independent Sample T-Test test, the p value = 0.000 (p <0.05) which means that there is an effect of boiled egg white on the healing of perineal lacerations in postpartum mothers. The results of this study indicate that there is a match between theory and facts in the field where the fulfillment of nutritional intake in postpartum mothers, especially foods rich in protein will help accelerate the healing of perineal lacerations. Protein from eggs is useful as a building block to replace damaged cells and help the formation of new tissue in accelerating the healing process of perineal laceration.